Odpowiedzi

2010-01-14T16:10:06+01:00
2010-01-14T16:14:22+01:00
A)
2* -2 + 3 +2 +6 +7*-2 =
-4+3+3+6-14 = -6

b)
2*5 + 0,1 - 3*5 + 4*0,1 - 1 =
10+ 0,1 - 15 + 0,4 - 1 = -5,5

c)
13*0,2 - 2*-1+7-9*0,2 - 1 - 4 + 0,2 - 3 =
2,6 + 2 + 7 - 1,8 - 1 - 4 + 0,2 - 3 = 2

d)
0,25 - 1/2 - 7 + 3* -1/2 + 1/2 - 9 + 1/2 + 16 = -0,375

:P.

mogło mi się źle policzyć. ^^"
4 1 4
2010-01-14T16:25:53+01:00
A) 2a + 3 - a + 6 + 7a = a + 16 = -2 + 16= 14
b) 2z + t - 3z + 4t - 1 = 5t - z - 1 = 5 * 0,1 - 5 - 1 = 0,5 - 5 - 1 = -5,5
c)13x - 2y + 7 - 9x + y - 4 + x - 3 = 5x - y = 5 * 0,2 - (-1) = 5 + 1 = 6
d)n² + n - 7 + 3n² - 9 - n + 16 = n² + 3n² = 4 * n² = 4 * ¼ = 1

W razie pytań pisz: [email protected]
Zawsze chętnie coś wytłumaczę i pomogę. :)
4 1 4